(untitled) (Research, Society and Development, 2021)
Lower Urinary Tract Dysfunction (DNTUI) or also known as Neurogenic Bladder (BN), refers to voiding disorders caused by neurological disorders in the Central or Peripheral Nervous System, where they cause changes in patients’ voiding patterns, especially in the bladder innervations. sphincter, and in the filling or emptying phases. Among the physical therapy interventions, electrical stimulation is a viable form of treatment, with good results, easy application, low cost and no side effects. The objectives of this review is to investigate the effectiveness of electrical stimulation in patients with neurogenic bladder in various neurological disorders . The electronic databases PubMed and SciELO were used. 10 studies were selected to carry out this review. The results showed that electrical stimulation in the posterior tibial nerve was used in 70% of the studies, appearing in the majority, while the use of electrical stimulation in the parasacral nerve was mentioned in 30% of the articles. The most used frequency was 20Hz and the pulse width ranged between 200 and 500 μs. The results showed a decrease in neurogenic bladder symptoms, regression of urinary losses and had a impact on bladder filling time. Therefore, it has been shown that the posterior tibial and parasacral nerves, as they are easily accessible, help in carrying out the treatment of the neurogenic bladder, making it safe and painless.